Fundamentals of Human Resource Management / Raymond A. Noe [et..al] - Noe, Raymond A.; Hollenbeck, John R.; Gerhart, Barry; Wright, Patrick M. (New York, NY : McGraw-Hill Education, 2018)
Provides a complete introduction to human resource management for the general business manager who wants to learn more about how HRM is used in the everyday work environment.
Part 1: The Human Resource EnvironmentChapter 1: Managing Human ResourcesChapter 2: Trends in Human Resource ManagementChapter 3: Providing Equal Employment Opportunity and a Safe WorkplaceChapter 4: Analyzing Work and Designing JobsPart 2: Acquiring, Training, and Developing Human ResourcesChapter 5: Planning for and Recruiting Human ResourcesChapter 6: Selecting Employees and Placing Them in JobsChapter 7: Training EmployeesChapter 8: Developing Employees for Future SuccessPart 3: Assessing and Improving PerformanceChapter 9: Creating and Maintaining High-Performance OrganizationsChapter 10: Managing Employees' PerformanceChapter 11: Separating and Retaining EmployeesPart 4: Compensating Human ResourcesChapter 12: Establishing a Pay StructureChapter 13: Recognizing Employee Contributions with PayChapter 14: Providing Employee BenefitsPart 5: Meeting Other HR GoalsChapter 15: Collective Bargaining and Labor Relations Chapter 16: Managing Human Resources Globally
BBS
STS International
Keywords: Personnel management; Business & finance